Composition optimization of mastic in recycled asphalt mixtures based on pavement performance - Xiaohui Li; Zhanghong Liu; Kaimin Fu; Kai Zhang; Maomao Chen (PLoS ONE, 2026)
Due to the depletion of natural sand and gravel resources and increasing environmental restrictions, the utilization of recycled asphalt pavement materials (RAP) has become a critical approach to mitigate the consumption of natural aggregates and reduce carbon emissions in highway construction. The performance of RAP-containing asphalt mixtures is closely associated with the properties of asphalt mastic, which consists of fine RAP (FRAP), fine natural aggregates, mineral filler, and asphalt binder. However, the interactions among these components, namely fine aggregate gradation (calculated via K value), mineral filler–binder ratio, and FRAP–fine aggregate ratio, are not yet fully understood, limiting the informed design of asphalt mastic. This study aims to investigate the compositional characteristics of asphalt mastic and propose an optimized gradation suitable for engineering applications. The results indicate that an asphalt mastic with a mineral filler–binder ratio of 1.4, a FRAP–fine aggregate ratio of 50:50, and a K value of 0.65 achieves optimal overall mechanical performance. An analysis of variance shows that the mineral filler–binder ratio is the dominant factor affecting mastic performance (p < 0.001), followed by the FRAP–fine aggregate ratio (p < 0.01), while the influence of the K value is comparatively weak. Building on these optimized mastic parameters, the effect of the coarse aggregate-to-asphalt mastic ratio was evaluated, with a ratio of 75:25 providing the most balanced mixture performance. Compared with the standard gradation, mixtures designed with the recommended gradation exhibited approximately 35% higher dynamic stability and 28% higher fracture toughness, indicating significantly improved resistance to rutting and cracking.